Rural,black and female: Educational Possibilities under severe conditions of constraints - Andreas, Letitia (School of Education, 2024)
The purpose of this minor dissertation is to investigate how a rural Black female from the Eastern Cape Province in South Africa achieves academic success in relation to a Historically White University (HWU) despite conditions of severe constraints. A narrative methodology is employed to contextualise the life experiences of three rural Black females in the broader context of South African histories of education, race, rurality, and gender. The study tracks the complex educational journey of a rural born South African female learner as she navigates between two disparate geographical, educational and social spaces. In this study, the data forms used are interview narratives generated from semi-interview transcripts and personal diary notes from interviews with the three rural Black females from the Eastern Cape. This research contributes to the fields of education, sociology, history, gender, rurality, and postcolonial studies. For data analysis of the three Rural Black Females' narratives, a narrative analysis is employed. The study shows how a rural Black female learner aspires to academic success in relation to schooling and a/an Historically White University (HWU) by drawing on a range of resources. In the face of many socioeconomic conditions of poverty in the Eastern Cape, a province still impacted by the violence of the Dutch and British settler colonial projects in South Africa, she frames an aspirational disposition. The aspirations of the rural Black female learner born in post-apartheid South Africa emerge from the rural context and schooling conditions that have socially and economically deprived the Black female aspirant body of adequate resources. The study finds that the rural female learner who attends a Historically White University is committed to academic success because she draws from the cultural context of an impoverished rural community in the Eastern Cape that is deeply underresourced, but more importantly, she draws from the humanness that is the 'human resource' (social network) around her that comprises her mother, sister, teachers, friends, peers, and a university support programme. She relies on her strong social relations and networks, as well as her agency and resilience, to navigate the legacies of racism, rural and urban spatial realities, personal dilemmas, patriarchal systems that discriminate against female bodies, and a range of family circumstances such as landlessness, livestock theft, poverty, unemployment, and migration. The study advances that rural learners' educational journeys are often undertheorised in relation to what constitutes ‘resources' available under conditions of resourceconstraints, and posits that the network of human-centred support is crucial to insert into such studies. The study demonstrates that, despite many constraints, there are a range of resources available to rural-born learners in order to foster an aspirational disposition toward achieving academic success.